Acoustic emission pulse analysis: an integrated system for transducer calibration and signal processing - Oliveras, Juan M. (Cranfield University, 1982)
The present thesis covers the pioneering effort of establishing an infrastructure for conducting research into the analysis of Acoustic Emission signatures, with emphasis being placed upon the recovery of the true surface waveform for a given transient input. The topics covered in this work are: The p·rovi s ion of the necessary computer software for the handling and processing of the data. Here, a method is included for the correction of phase errors introduced by the sampling/multiplexing of ·the signals, which provides the basis for the implementation of data convolution.techniques in the frequency domain. J°he development of an experimental rig and source of excitation, later applied to the design of transducers. The development of a new transducer configuration, capable of producing a relatively flat frequency response (±7dB) over the frequency range 300 KHz - 2 MHz. The development of a procedure for the calibration of transducers, based upon a modified reciprocity method. The technique produces the calibration of transducers in relative terms, requiring a comple- . . mentary method to provide the reference level for the calibration. As a means of assessing the proposed techniques, the transducer calibration was applied to the de-convolution of pulses generated with a step forcing function, and the results compared with an equivalent theoretical model previously published.